Immune aberrations in children with Autism Spectrum Disorder: a case-control study from a tertiary care neuropsychiatric hospital in India - Basheer, Salah; Venkataswamy, Manjunatha M.; Christopher, Rita; Van Amelsvoort, Therese; Srinath, Shoba; Girimaji, Satish Chandra; Ravi, Vasanthapuram (Psychoneuroendocrinology, 2018)
•This is the first study to comprehensively evaluate various peripheral immune cell subsets coupled with associated serum cytokine levels in children with ASD.•Myeloid dendritic cells and activated Th17 cells were significantly elevated in children with ASD.•Serum IL-6 levels and IL-17 levels were higher in children with ASD.•Study findings provide concurrent and converging evidence for the activation of Th17 pathway in ASD. Multiple studies have identified the presence of peripheral immune aberrations in subjects with Autism Spectrum Disorder (ASD). However, comprehensive assessment of these peripheral immune aberrations, in the cellular and systemic compartments, in a single group of subjects with ASD is lacking. We assessed proportions of various subsets of immune cells in peripheral blood (T helper cells, T regulatory cells, B cells, monocytes, Natural Killer cells, dendritic cells) by multi-parametric flow cytometry in 50 children with ASD and compared it with thirty healthy controls matched for age, gender, socio-economic status and body mass index. There were no significant differences noted in the proportion of T regulatory cells, B cells, monocytes and Natural Killer cells, between ASD subjects and controls. On the contrary, the proportion of activated Th17 and myeloid dendritic cells were significantly higher in children with ASD. Based on these findings, group comparison of serum levels of Th17 cytokines (interleukin-6, interleukin-17A) was performed. Elevated serum levels of interleukin-6 and interleukin-17A in children with ASD corroborated our immunophenotyping findings. We did not find any significant differences among the pro-inflammatory (interleukin-1β), Th1 (interferon-γ) and Th2 (interleukin-4) cytokines. This is the first evidence with concurrent findings from immunophenotyping and cytokine data demonstrating activation of the Th17 pathway in subjects with ASD. This finding assumes significance in the light of recent maternal immune activation mouse model study that has highlighted the role of Th17 pathway in the pathophysiology of ASD. Future longitudinal studies are needed to clarify the role of this dysregulated immune pathway in the development of ASD.